Sunlight-exposure photodimerization behavior of some 7,8-ethylenedioxycoumarins: Experimental and theoretical evidence of photodimerization - (:unkn) unknown (ELSEVIER, 2014)
Sunlight-exposure photodimerization properties of recently synthesized 7,8-ethylenedioxycoumarin (I) and 7,8-ethylenedioxy-4-methyl coumarin (II) were studied with respect to exposure time and pH in 5% v/v aqueous methanol by electronic absorption spectra. I was found to undergo a reversible [2 + 2] photodimerization upon exposure to sunlight only in basic solutions. In contrast, II was not found to undergo photodimerization upon exposure to sunlight either in acidic or basic solutions. The dimer formation constant was determined as pK(Dimer) = 10.650 (R-2 = 0.9999). A photodimerization mechanism consistent with the experimental results was proposed, which is consistent with the experimental results. In addition, quantum chemical calculations showed agreement with the experimental evidence. The role of methyl group of II on the sunlight-exposure photochemical properties of ethylenedioxycoumarins was discussed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ethylenedioxycoumarins; Flavonoids; Sunlight-exposure photodimerization; ACID-BASE EQUILIBRIA; PYRIMIDINE-DERIVATIVES; COUMARIN-6-SULFONYL CHLORIDE; ELECTROCHEMICAL-BEHAVIOR; ELECTRONIC ABSORPTION; PH MEASUREMENTS; COUMARIN; CATALYSIS; POLYMERS; RELEASE